Ecoturismo: Potencialidades e Limitações Ambientais do Município de São José dos Ausentes, RS / Ecotourism: Potential and Environmental Limitations in São José dos Ausentes, Brazil - Casagrande, Verônica; Schneider, Vania Elisabete; Cemin, Gisele; Bortolin, Taison Anderson (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2015)
O Turismo apresenta índices de crescimento no contexto econômico mundial, sendo o ecoturismo um dos segmento de maior desenvolvimento. O ecoturismo é contemplado no turismo rural, apresentando como vantagem incremento dos rendimentos nas propriedades rurais e a redução do êxodo rural pela geração de emprego e renda. Da mesma forma que para outras atividades, os impactos socioambientais do ecoturismo também devem ser avaliados, como o aumento da geração de resíduos em períodos específicos e a descaracterização do meio para a instalação de novas estruturas. Neste contexto, são apresentados os aspectos ambientais de São José dos Ausentes, no Rio Grande do Sul, e o desenvolvimento do ecoturismo no local, destacando as potencialidades e as fragilidades ambientais a serem observadas e consideradas na fase de planejamento das atividades no município. A opção pela aplicação do estudo neste município provém da potencialidade turística em contraponto às atuais ações antrópicas impactantes que vem ocorrendo na região. Palavras-chave: Turismo Rural. Ecoturismo. Planejamento ambiental. Impactos ambientais. São José dos Ausentes, RS. Ecotourism: Potential and Environmental Limitations in São José dos Ausentes, Brazil - Tourism has the highest growth rates in the world economic context, and the ecotourism segment of further development. The ecotourism is contemplated in rural tourism, having as main advantage the increase in the income of landowners. As a benefit of this model, it can be highlighted the contribution to the reduction of the rural exodus, with the expansion employment and income generation. The same way as for other activities, the social and environmental impacts of ecotourism should also be evaluated, such as increased waste generation in specific periods and the mischaracterization of the medium for the installation of new structures. In this context, the environmental aspects of São José dos Ausentes and the development of ecotourism at the site are presented, highlighting the strengths and weaknesses environmental, to be observed and considered in the planning phase of ecotourism activities in the municipality. The option of study for this municipality comes from the tourism potential and current anthropogenic impactful actions occurring in the region. Keywords: Rural Tourism. Ecoturism. Environmental Planning. Environmental Impacts. São José dos Ausentes, Brazil.